Strategi Pengembangan Desa Wisata Timpag Berbasis Masyarakat di Kecamatan Kerambitan, Kabupaten Tabanan Bali - Gusti Ayu Putu Marwangi; I Putu Anom (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Tabanan Regency has a high prospect in the development of tourism and its complementary facilities. Tourism village is the alternative tourism products that can provide the development of rural areas that are certainly sustainable for the future. Timpag Village is one of the villages which located in Kerambitan District, Tabanan Regency which has several tourism potentials such as nature, cultures, and the local communities. The development of Rural Tourism in Timpag Village has a high value to be a tourist attraction but the reality this village has not been able to be a developed as a rural tourism. Based on these problems this research aims to determine “Development Strategies of Rural Tourism Based Local Community in Timpag Village, Kerambitan District, Tabanan Regency Bali.” The research method used in this study is a qualitative descriptive analysis supported by IFAS and EFAS analysis in designing a strategy for developing local community-based tourism villages used SWOT analysis. Data collection techniques are using the method of observation, interviews, library research. The result show the design of alternative strategies to develop community-based tourism villages that can be applied in the development of Rural Tourism in Timpag Village. There are six altrenative strategys that can be applied such as attractions development based on tourism potential, local communities involvement , tourism facilities development, tourism organisation development, improve the traditional security system, and improve the ability of communities about tourism development. Therefore, local communities need to preserve the tourism potential that is owned as a rural tourism product. Keywords: Rural Tourism, Community Based Tourism, and Strategy